The Relationship between Body Mass Index with Knowledge and Energy Intake in Diabetic Patients in Prolanis Club - Nuswantari, Atika; Dewi, Yulia Lanti Retno; Rahardjo, Setyo Sri (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
The prevalence of diabetes mellitus in Indonesia is 2.0%, while East Java ranks 5th, higher than the national prevalence. According to data from the Jombang Regency Health Office, the outpatient diabetes mellitus cases at the Community Health Centers presented on the Indonesia Statistics of Jombang Regency website were 10,133 in 2013, 12,765 in 2014, and 21,992 in 2015, indicating an upward trend in the number of diabetes mellitus patients each year. Insulin resistance is the main cause of diabetes mellitus as a degenerative disease. Information on proper diabetes mellitus health management is expected to enhance knowledge as a means of improving individual behavior and actions. The prevention of diabetes mellitus can be achieved through a healthy lifestyle, which includes regulated and measured eating patterns and physical activity. The objective of this study is to determine the relationship between body mass index with knowledge and energy intake in diabetic patients. This correlational study employed a cross-sectional method involving 60 subjects from three Community Health Centers in Jombang Regency, comprising 54 female and 6 male subjects. Data collection was conducted using a questionnaire instrument with interview techniques and analyzed using the Kolmogorov-Smirnov normality test. Data did not have a normal distribution and were subsequently tested with Spearman correlation. The study shows a significant relationship between body mass index and knowledge p = 0.041 with a moderate correlation strength (r = -0.265*) relationship between the variables. The relationship between body mass index and energy intake shows a significant correlation p = < 0.01 with a correlation coefficient of 0.695*, indicating a strong relationship. Conclusion: Body mass index (BMI) has a significant relationship and a moderate correlation strength with knowledge of diabetes diet. The correlation between BMI and the dietary intake of individuals with diabetes mellitus is significant and strong correlation strength. Periodic and easy implement diabetes mellitus diet education is recommended and is expected to increase knowledge so that energy intake is adequate and appropriate to their needs.